Urban sketching : the complete guide to techniques - Thorspecken, Thomas (Hauppauge, NY : Barron's Educational Series, Inc., 2014)
'While most sketching guides leave the artist with static bowls of fruit and boring vases of flowers to develop their skill, Urban Sketching takes its inspiration from the living, breathing world around us.'--Back cover.
Chapter 1. Tools and techniques -- Chapter 2. Going urban -- Chapter 3. Populating your world -- Chapter 4. Choosing a subject.
'A Quarto Book.'
Includes bibliographical references (page 128) and index.
Keywords: Drawing -- Technique; Cities and towns in art; City and town life in art